Turkish Society of Gastroenterology: Pancreas Working Group, Acute Pancreatitis Committee Consensus Report - Deniz Öğütmen Koç; Göksel Bengi; Özlem Gül; Yeşim Özen Alahdab; Engin Altıntaş; Sezgin Barutçu; Yılmaz Bilgiç; Birol Bostancı; Mehmet Cindoruk; Kadri Çolakoğlu; Deniz Duman; Nergiz Ekmen; et al. (The Turkish Journal of Gastroenterology)
Acute pancreatitis (AP) is a clinical condition that arises acutely in the pancreas through various inflammatory pathways due to multiple causes. Turkish Society of Gastroenterology Pancreas Working Group developed comprehensive guidance statements regarding the management of AP that include its epidemiology, etiology, clinical presentation, diagnostic criteria, disease severity, treatment, prognosis, local and systemic complications. The statements were developed through literature review, deliberation, and consensus opinion. These statements were ultimately used to develop a conceptual framework for the multidisciplinary management of AP.